Similar digit-based working memory in deaf signers and hearing non-signers despite digit span differences - Andin, Josefine; Orfanidou, Eleni; Cardin, Velia; Holmer, Emil; Capek, Cheryl M.; Woll, Bencie; Rönnberg, Jerker; Rudner, Mary (Frontiers in Psychology, 2013)
Similar working memory (WM) for lexical items has been demonstrated for signers and non-signers while short-term memory (STM) is regularly poorer in deaf than hearing individuals. In the present study, we investigated digit-based WM and STM in Swedish and British deaf signers and hearing non-signers. To maintain good experimental control we used printed stimuli throughout and held response mode constant across groups. We showed that deaf signers have similar digit-based WM performance, despite shorter digit spans, compared to well-matched hearing non-signers. We found no difference between signers and non-signers on STM span for letters chosen to minimize phonological similarity or in the effects of recall direction. This set of findings indicates that similar WM for signers and non-signers can be generalized from lexical items to digits and suggests that poorer STM in deaf signers compared to hearing non-signers may be due to differences in phonological similarity across the language modalities of sign and speech.